Phenotypic characterization of six Indonesian local chicken populations - Yuli Arif Tribudi; Veronica Margareta Ani Nurgiartiningsih; Maria Ulfah; Muhammad Halim Natsir; Dyah Maharani; Aprilianna Putri Zahara Nafsina Luvita Sari; Irwan Lovadi; Richard Crooijmans; Danung Nur Adli; Dwi Nur Happy Hariyono; Alek Ibrahim (Cogent Food & Agriculture)
Local chicken populations are vital to the livelihoods and nutrition of rural communities in Indonesia. This study characterized six local populations—Nunukan, Merawang, Tukong-Kalimantan, Tukong-Java, Kampung-Kalimantan, and Kampung-Java—based on the morphological traits of 203 randomly selected chickens. Significant differences were observed in plumage, shank, comb, earlobe, eye, and beak colour across populations, except between Nunukan and Merawang. Kampung-Java chickens had the highest body weight and measurements, while Tukong-Kalimantan showed the lowest values and distinctive features such as rumplessness and shorter back lengths. Morphometric analysis identified tibia and femur lengths as key distinguishing traits, along with wing and breast dimensions. Cluster analysis grouped Tukong-Kalimantan separately from the other populations, which formed three subclusters. In summary, support the conservation and genetic improvement of Indonesian local chickens and underscore the importance of phenotypic traits, especially limb characteristics and rumplessness, for selective breeding.